Multimorbidity predicts falls differentially according to the type of fall in postmenopausal women. (September 2016) - Afrin, Nadia; Honkanen, Risto; Koivumaa-Honkanen, Heli; Lukkala, Pyry; Rikkonen, Toni; Sirola, Joonas; Williams, Lana J.; Kröger, Heikki
Highlights: We assessed whether morbidity predicts falls differentially according to the type of fall. The large study population (of 10, 594 women) was drawn from an osteoporosis study (OSTPRE, Finland). The fall risk increased with number of chronic medical conditions. This risk was notably greater for nonslip than for slip falls. Abstract: Objective: To ascertain whether the risk of falls of different types is related to morbidity (number of chronic medical conditions) among postmenopausal women. Study design: This cohort study uses data from a population-based prospective cohort study (OSTPRE). The study population consisted of 10, 594 women aged 47–56 years living in Kuopio Province, Eastern Finland, in 1989, who responded to postal enquiries at both baseline and 5-year follow-up, in 1994. Morbidity (i.e. number of diagnosed chronic medical conditions) was reported in 1989 and falls in 1994. Falls were categorized as slip or nonslip, and 'frequent falls' was defined as two or more in a 12-month period. Results: The risk (odds ratio (OR) with 95% CI) of a fall increased with the number of chronic medical conditions. The OR was 1.28 (1.17–1.40) for those with 1–2 conditions and 1.41 (1.24–1.60) for those with multimorbidity (≥3 conditions) compared with healthy respondents. Multimorbidity was associated with a greater risk of the woman experiencing frequent nonslip falls (OR = 2.57; 2.01–3.29) than frequent slip falls (OR = 1.46; 1.17–1.80). Adjusting with logistic regression for age, number of medications and smoking did not affect the risk estimates. Conclusion: Multimorbidity has a much smaller effect on slip than on nonslip falls in postmenopausal women. This should be taken into account when investigating the effects of multimorbidity on fall risk in varying weather conditions.